Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2016)
In this issue, six articles are presented analyzing quite different issues and using very different methods. A common denominator for all of the articles is, however, that they examine new trends and issues in work life, discussed in the public debate and experienced in the working life of many employees. Two articles highlight the current trend toward a labor market with temporary and precarious employment: One article examines artists’ work orientation and working conditions. Artists have a long tradition of working in employment arrangements that increasingly characterize the current labor market. Another article explores how our understanding of temporary migrant care workers is constructed. A third article contributes to our understanding of the effect of New Public Management on working conditions: the article analyzes coping and resistance when employees in the public sector experience moral distress as a result of New Public Management. Personality seems to have increasing importance in the differentiation at the labor market. A fourth article examines how the assessment of personality actually is performed by recruitment consultancies. Two articles examine the opportunities to improve working conditions under the new conditions: One article examines the effects of interventions designed to improve the work-life reconciliation. Another article examines the public regulation of the psychosocial work environment (...)